2019
DOI: 10.37077/25200860.2019.275
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moringa oleifera Leaf Meal and their Aqueous and Ethanolic Extracts on Immunological Parameters, and Liver Enzymes of Broiler Chickens

Abstract: The purpose of this study is to investigate the effect of Moringa oleifera leaf meal and their aqueous and ethanolic extracts on immunological parameters, economic results and liver enzymes of broiler chickens. Two hundred and ten unsexed day-old Ross308 broiler chicks were divided into seven experimental diets . Each treatment had three replicates with 10 birds per replicate. Each replicate was fed with an assigned experimental diet for five weeks. The treatments were as follows:T1 was the control without add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The results of the statistical analysis Table (2) The effect of adding imported PFA on the body weight (g) of broiler chickens indicated that there were significant differences between the treatments at the level (P ≤ 0.05), and all treatments had a significant improvement in live body weight compared to the control treatment (without addition ) as it was T4 , T7 1983.40 , 1965.43 , respectively, compared to T1, which amounted to 1737.36 , as the addition of dry and liquid PFA all brought positive results in the live body weight of broiler chickens, and the reason for this is due to the presence of active and biologically active substances in both additions [15]. As the reason for improving liver enzymes and other antioxidant enzymes in the blood serum of birds is due to the active substances present in the plant additive PFA, as it contains natural antioxidants that suppress free radicals and thus reduce oxidative stress, which is beneficial to the general health of birds and thus to the traits Bird productivity [13]. that there are significant differences between the treatments at the level (P ≤ 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the statistical analysis Table (2) The effect of adding imported PFA on the body weight (g) of broiler chickens indicated that there were significant differences between the treatments at the level (P ≤ 0.05), and all treatments had a significant improvement in live body weight compared to the control treatment (without addition ) as it was T4 , T7 1983.40 , 1965.43 , respectively, compared to T1, which amounted to 1737.36 , as the addition of dry and liquid PFA all brought positive results in the live body weight of broiler chickens, and the reason for this is due to the presence of active and biologically active substances in both additions [15]. As the reason for improving liver enzymes and other antioxidant enzymes in the blood serum of birds is due to the active substances present in the plant additive PFA, as it contains natural antioxidants that suppress free radicals and thus reduce oxidative stress, which is beneficial to the general health of birds and thus to the traits Bird productivity [13]. that there are significant differences between the treatments at the level (P ≤ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the use of Phytogenic Plant Additives (PFA), which consists of a group of medicinal plants and their oils, is common due to the fact that these plants possess effective and biologically active substances to stimulate growth, increase production, and reduce mortality as a result of improving the health status of animals and enhance immune system [4][5][6]. These vegetable additives also contain fatsoluble vitamins (A, D, E, and K), which contribute to increased absorption and digestion of lipoproteins [7]. Aromatic plants and spices contain biologically active substances that stimulate the digestion process and the production of digestive enzymes because they contain many active compounds and chemicals such as anothiol, econol [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Table (5) showed the effect of adding the synergistic mixture of oyster mushroom and beta-glucan on the amount of feed consumed during the first week of the experiment as no significant differences appeared between all treatments. There was a significant difference between the treatments at the second, third, fourth and fifth weeks, in addition to, the cumulative feed quantity, the amount of feed consumed decreased as a result of exposure birds to heat stress in all treatments except for the fourth treatment which was superior significantly (P<0.05) it was recorded 2772.59 g compared to the third, second and control treatment , which were (2678.12, 2620.10, 2580.75) g, respectively results in table (6) showed the effect of adding the synergistic mixture of oyster mushroom and beta-glucan on the efficiency of food conversion.…”
Section: Amount Of Feed Consumed and Feed Conversion Efficiencymentioning
confidence: 99%
“…The main problems facing animal production in countries with tropical and subtropical climates is heat stress, which negatively affects the performance of poultry [4]. Researchers were interested in using some strategies to find out their effect on some immune traits of broiler chickens, including vegetable additives [5]. Studies were conducted on the genetic side of chickens exposed to heat stress in order to predict the ability of birds to withstand stress conditions [6] [7], [8], showed that heat stress leads to changes in the bacterial content of the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the harm caused by the antibiotics used in feeding poultry to human and animal health through the resistance of pathogens and their residues in poultry meat (Soltan et al, 2008;Dalkili & Guler, 2009). So, the researchers tended to use medicinal plants and herbs as safe feed additives in poultry diets, as they have a positive role in stimulating growth , improving the immune system and physiological traits of birds (Jugl-Chizzola et al, 2006;Özer et al, 2007;Al-Salhie & Al-Waeli, 2019;Hussein & Jassim, 2019;Sultan et al, 2019;Al-Salhie & Makki, 2020). In addition to stimulating beneficial microorganisms within the intestines of birds, which contributes to the digestion of many nutrients and make them available to birds (Tekeli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%